Найдите значение алгебрического выражения при х=2,у=-3: а) (2х+у)^2 b) 4x^2-2xy+y^2; в) (-2x+y)^2; г) 4x^2+4xy+y^2; д) (-2x-y)^2; e) (-2x)^2-2*2xy+y^2; ж) (2x-y)^2; з) (-2x)^2+2(-2x)y+y^2; и) (-2x)^2*2xy+(-y)^2. Помогите пожлау...
Найдите значение алгебрического выражения при х=2,у=-3:
а) (2х+у)^2
b) 4x^2-2xy+y^2;
в) (-2x+y)^2;
г) 4x^2+4xy+y^2;
д) (-2x-y)^2;
e) (-2x)^2-2*2xy+y^2;
ж) (2x-y)^2;
з) (-2x)^2+2(-2x)y+y^2;
и) (-2x)^2*2xy+(-y)^2.
Помогите пожлауйста очень надо
Ответ(ы) на вопрос:
Гость
[latex]x=2,\; y=-3\\\\b)\; 4x^2-2xy+y^2=(2x-y)^2+2xy=(4+3)^2+12=61\\\\g)\; 4x^2+4xy+y^2=(2x+y)^2=(4+9)^2=169\\\\e)\; (-2x)^2-2\cdot 2xy+y^2=4x^2-4xy+y^2=(2x-y)^2=(4+3)^2=49\\\\z)\; (-2x)^2+2(-2x)y+y^2=4x^2-4xy+y^2=(2x-y)^2=49\\\\u)\; (-2x)^2\cdot 2xy+(-y)^2=4x^2\cdot 2xy+y^2=16\cdot (-12)+9=-183\\\\u_1)\; (-2x)^2+2xy+(-y)^2=4x^2+2xy+y^2=(2x+y)^2-2xy=\\\\=169+12=181\\\\u_2)\; (-2x)^2-2xy+(-y)^2=4x^2-2xy+y^2=(2x-y)^2+4xy=\\\\=49-24=25\\[/latex]
Не нашли ответ?
Похожие вопросы